Gender Differences in University Student-Athletes' Expressed Levels of Academic and Athletic Motivation - Snyder, Peter L. (My University, 1993)
The purpose of this study was to examine possible differences between male and female student-athletes in regard to their expressed levels of academic versus athletic motivation. A survey conducted among 670 student-athletes at five campuses of a large western university system revealed differences between males and females in the level of motivation they expressed for pursuing athletic versus academic success. The survey included a 4 point Likert scale assigned by response for seven scenarios: road trip, preregistration, field trip, graduation choice, final exam study, roommate choice and late start opions. Teams on three of the campuses surveyed compete at the Division I level, whereas teams on the remaining two compete in Division III. At both divisional levels, females expressed greater academic motivation than did their male counterparts. Implications of these results for university administrators and counselors were discussed.
Keywords: skills; identity; Division III; Division I; sex/gender; demographics